2020
DOI: 10.3390/smartcities3030049
|View full text |Cite
|
Sign up to set email alerts
|

Replicating Smart Cities: The City-to-City Learning Programme in the Replicate EC-H2020-SCC Project

Abstract: This article addresses the problem of replication among smart cities in the European Commission’s Horizon 2020: Smart Cities and Communities (EC-H2020-SCC) framework programme. This article initially sets the general policy context by conducting a benchmarking about the explicit replication strategies followed by each of the 17 ongoing EC-H2020-SCC lighthouse projects. This article aims to shed light on the following research question: Why might replication not be happening among smart cities as a unidirection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 54 publications
1
25
0
4
Order By: Relevance
“…In the prospects of future research addressing democratic legitimacy-related questions smart cities face, this article shed light on a further nuanced empirical demonstration regarding the penta-helix framework playing a role in creating less technocratic smart cities. The penta-helix thus represents in itself a methodological innovation with social added value by acknowledging that each city or region may present a different democratic context in which stakeholders operate and interact in relatively unique terms [1,54,110]. Apart from addressing the research questions, this article encourages scholars to follow the methodological rationale that was suggested by taking up comparative case study research that highlights novel analytical practices carried out in the broad SCC H2020 European framework bringing together no less than 93 European smart cities, which, in itself, is an opportunity to further explore the research questions elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the prospects of future research addressing democratic legitimacy-related questions smart cities face, this article shed light on a further nuanced empirical demonstration regarding the penta-helix framework playing a role in creating less technocratic smart cities. The penta-helix thus represents in itself a methodological innovation with social added value by acknowledging that each city or region may present a different democratic context in which stakeholders operate and interact in relatively unique terms [1,54,110]. Apart from addressing the research questions, this article encourages scholars to follow the methodological rationale that was suggested by taking up comparative case study research that highlights novel analytical practices carried out in the broad SCC H2020 European framework bringing together no less than 93 European smart cities, which, in itself, is an opportunity to further explore the research questions elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The research revealed key qualitative observations and mapped out evidence-based empirical results on the five strategic dimensions studied in each follower city: (i) the composition of stakeholders per helix; (ii) the most influential stakeholder-helix; (iii) the most proactive stakeholder-helix; (iv) knowledge on the PPP; and ultimately, (v) the most suitable business/social model (per smart city sector too) in each follower city. The results were obtained in each city comparatively for the three Replicate follower cities (www.replicate-project.eu/city2citylearning) based on in-depth interviews with a selected group of 25 strategic stakeholders representing the penta-helix framework through in-depth interviews and later validated later through a workshop (Table A1 in the Appendix A section) [54]. The five strategic dimensions inferred from the literature review and the results of the empirical research were used to build the comparative methodology of the three cases, which addresses the research questions of this article, presented in the Introduction section.…”
Section: Methodology: Mapping Out the Penta-helix Multistakeholder Pomentioning
confidence: 99%
See 2 more Smart Citations
“…This policy framework enables the creation of open data and personal data stores for mutual benefit, possibly slowing the unbridled extraction of personal data by big tech private "data-opolies". City-regional authorities could establish data co-operatives to empower citizens to gain more control over their data, and allow them more of a say in the services built on and informed by these data [110,111]. Such practices may help to rebalance the relationship between those who create data (citizens) and those who seek to exploit those data, while creating an environment for fair and democratic exchange [112].…”
Section: Research Design and Methodology: The Research Question Two mentioning
confidence: 99%